The Impact of a School Dog on Children's Social Inclusion and Social Climate in a School Class - Mona M. Mombeck; Timm Albers (MDPI AG, 2023)
Animal-assisted pedagogy is well known in classroom practice, but scientific evidence of its impact on teaching and learning conditions is still lacking. At the same time, the biggest challenge in education systems worldwide is the social inclusion of students. In a pre-post design, 30 heterogeneous students (16 f/14 m) from four different school classes (grades 5-8) of two secondary schools and one grammar school were interviewed (in a problem-centered interview) about their social inclusion and their social climate in class before and after being taught selected subjects with a school dog for one school term. At the second measurement point, participants were also asked about their perception of animal-assisted pedagogy. The qualitative data analysis (Kuckartz) showed that the presence of a dog leads to an improved social climate, more social integration and to a change in social roles; therefore, we discussed our findings in the context of role theory (Krappmann). In addition, we found that the mutual perception of the other students and the teacher changes to a more positive and friendlier image. Through animal-assisted pedagogy, a new social role is added to the classroom, where caring and bonding are prioritized. Social interaction and norms are influenced and stereotypical and individual roles can be changed. Therefore, animal-assisted pedagogy can be key to promoting social inclusion in the school environment.